Les novel·les sobre la Transició valenciana. Una història de claudicacions i violència. - ESPINÓS FELIPE, JOAQUIM (Scripta, 2019)
The Spanish Transition (1975-1982) is a controversial historical period. In recent years, following the 15-M movement, we have witnessed in Spain a revival of voices critical of the official narrative. In the Valencian area there is a considerable corpus of novels that provide relevant information on the way how the memory of the Valencian Transition has been built. The distance existing between the present and the years in which the facts took place, as well as the ignorance of the new generations on the subject, allows us to consider these novels, in a broad sense, as historical novels, at the same level as those set in the Civil War and the post-war period.